THE IMPLEMENTATION OF REFUTATION TEXT IN REMEDIATION OF STUDENTS MISCONCEPTIONS IN CHEMICAL EQUILIBRIUM - F02112026, Sugandi; Enawaty, Eny; Sartika, Rody Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract : This research aims to know the differences the students learning outcome before and after remediation with the effectiveness of remediation by using refutation text in reducing the students misconceptions at XI IPA of SMA Negeri 1 Sungai Ambawang in the academic year 2015/2016 on the chemical equilibrium matter. The form of this research is a quasi-experimental (Pre-Experimental Design) by One-Group Pre-Test Post-Test design. The data processed are 26 students by using purposive sampling technique. The test used is diagnostic test in form of essay questions. Based on the analysis of the data, the decrease average percentage of the students misconception is 45,6%. The difference in the students learning outcome tested with paired t-test and the results of the significance obtained 0,000. The effectiveness of remediation toward refutation text in chemical equilibrium concepts is 0.54 and classified as medium category. Remediation by using refutation text is effective in reducing the students misconception. Key Words: refutation text, remediation, misconceptions.